Implementasi Pendekatan Jelajah Alam Sekitar Terintegrasi Project-Based Learning untuk Meningkatkan Keterampilan Proses Sains Biologi : (Implementation of Exploring Nature Approach Integrated with (Project-Based Learning) to Improve Biology Science Process Skills) - Rahimanisa, Fadillah; Marjanah, Marjanah; Khalil, Muhammad (BIODIK, 2025)
Science process skills are skills that help students acquire and develop knowledge through direct observation of natural phenomena. SPS is important for students because it makes students more active, trains their questioning skills, and improves their understanding of subject matter through real experiences. This study aims to evaluate the effectiveness of the implementation of an integrated project-based learning nature exploration approach in improving biology SPS. This quantitative study used a pre-experimental approach with a one group pretest-posttest design. The study was conducted at SMAN 4 Langsa in May 2024 with a sample of 24 grade X students from a total population of 44 students. The research instruments used were pretest-posttest questions and SPS observation sheets. Data were analyzed using SPSS to see changes in skills before and after learning. The results showed an increase in SPS, with an average pretest score of 64.5 and a posttest of 84.8. The N-Gain obtained was 0.59, indicating a moderate increase. The average score of students' SPS> 82.3, indicating that aspects of skills such as observing, grouping, and planning experiments had increased. In conclusion, the integrated PjBL nature exploration approach effectively improves students' KPS. The implication is that this approach can be used as an effective innovative learning strategy to facilitate understanding of biological concepts and improve students' scientific skills through exploration of the surrounding environment. Abstrak. Keterampilan proses sains merupakan keterampilan yang membantu siswa memperoleh dan mengembangkan pengetahuan melalui observasi langsung fenomena alam. KPS penting bagi siswa karena membuat siswa lebih aktif, melatih kemampuan bertanya, dan meningkatkan pemahaman materi pelajaran melalui pengalaman nyata. Penelitian ini bertujuan mengevaluasi efektivitas implementasi pendekatan jelajah alam sekitar terintegrasi project-based learning dalam meningkatkan KPS biologi. Penelitian kuantitatif ini menggunakan pendekatan pre-eksperimental dengan one group pretest-posttest design. Penelitian dilaksanakan di SMAN 4 Langsa pada Mei 2024 dengan sampel 24 siswa kelas X dari total populasi 44 siswa. Instrumen penelitian yang digunakan adalah soal pretest-posttest dan lembar observasi KPS. Data dianalisis menggunakan SPSS untuk melihat perubahan keterampilan sebelum dan sesudah pembelajaran. Hasil penelitian menunjukkan peningkatan KPS, dengan nilai rata-rata pretest 64.5 dan posttest 84.8. N-Gain yang diperoleh 0.59, menunjukkan peningkatan kategori sedang. Skor rata-rata KPS siswa >82.3, menunjukkan aspek keterampilan seperti mengamati, mengelompokkan, dan merencanakan percobaan mengalami peningkatan. Kesimpulannya, pendekatan jelajah alam sekitar terintegrasi PjBL efektif meningkatkan KPS siswa. Implikasinya, pendekatan ini dapat digunakan sebagai strategi pembelajaran inovatif yang efektif untuk memfasilitasi pemahaman konsep biologi dan meningkatkan keterampilan ilmiah siswa melalui eksplorasi lingkungan sekitar.